STRATEGI PENANGANAN ANAK JALANAN DI KOTA SEMARANG - Dwi Ratih Chaeroti; Dyah Hariani; Aufarul Marom (Journal of Public Policy and Management Review, 2013)
The Purpose of this study is to conduct and analysis the condition of handling of street children in Social Agency of youth and sports of Semarang by using internal environment analysis organization. Analysis of the internal and external environment organisation aiming to found out the factors restridting developmentand support in the handling of street children. In conducting the analysis the condition of the handling of the street children, the researchers use a SWOT analysis (Strenght, Weaknes, Opportunities, threats). This research uses qualitative research methods, descriptive by using informants from the Social Department of Youth and Sports of Semarang, as well as the public, and members of NGOS.The results of research strategies for handling in the form of a street children Social Department of Youth and Sports of Semarang shows the condition handling street children pertaining to the conditions outside the internal and external in department has been good enough but that are still some disadvantages. To do the analysis afterwards, the internal and external this environment out of the comes factors are the economy and supporters that effects formularization strategy which will then in a test by using litmus test to measure the strategies program that exist.From the results of such research, it is recomanded that the strategic programmes have been formulated are implemented consistently and further enhanced by opening the possibility for the emergence of positive innovations in its implementation.